2008
DOI: 10.1021/jf801383m
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Effect on the Structure of β-Lactoglobulin B and Its Ligand Binding

Abstract: The changes of structure and ligand binding properties of beta-LG B have been studied by fluorescence and circular dichroism spectroscopy in ethanolic solutions. Fluorescence measurements of retinol/beta-LG interactions at 480 nm in various ethanol concentrations show that the maximal fluorescence intensity induced by this interaction between retinol and beta-LG is observed around 20% v/v of ethanol. It is reduced to zero at 40% and 50% of ethanol. These results suggest that there are two distinct structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The protein fluorescence intensity decreased to about 51% in the presence of 10 µM retinol, with a new λ max appearing around 480 nm (curve c in Figure 5A), attributed to retinol. 40 Addition of FA decreased the retinol fluorescence intensity, indicating the occurrence of FA-induced retinol fluorescence quenching. Normalized relative to fluorescence intensity of the β-LG-retinol mixture at λ max (right ordinate axis), FA decreased the β-LG fluorescence intensity in the presence of retinol to about 66% (curve d in Figure 5A), very close to the value obtained in the absence of retinol.…”
Section: Resultsmentioning
confidence: 94%
“…The protein fluorescence intensity decreased to about 51% in the presence of 10 µM retinol, with a new λ max appearing around 480 nm (curve c in Figure 5A), attributed to retinol. 40 Addition of FA decreased the retinol fluorescence intensity, indicating the occurrence of FA-induced retinol fluorescence quenching. Normalized relative to fluorescence intensity of the β-LG-retinol mixture at λ max (right ordinate axis), FA decreased the β-LG fluorescence intensity in the presence of retinol to about 66% (curve d in Figure 5A), very close to the value obtained in the absence of retinol.…”
Section: Resultsmentioning
confidence: 94%
“…At a relatively higher concentration (2.0 mmol L –1 ), the bands at 266 and 286 nm were retained; however, the other two bands could not be observed and indicates partial sustenance of the 3° structure. In the presence of biamphiphilic SAIL-4, the tertiary structure of the βLG was almost retained up to C 2 ; however, further increase in the concentration up to C 3(cmc) resulted in the total collapse of the 3° structure and attained a structure characteristic of molten globular state . Such a huge structural change could be due to the increased hydrophobic interactions of protein with the SAIL-4 caused by the two longer alkyl chains present in both the cation and anion unlike in the other three SAILs.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of biamphiphilic SAIL-4, the tertiary structure of the βLG was almost retained up to C 2 ; however, further increase in the concentration up to C 3(cmc) resulted in the total collapse of the 3°structure and attained a structure characteristic of molten globular state. 66 Such a huge structural change could be due to the increased hydrophobic interactions of protein with the SAIL-4 caused by the two longer alkyl chains present in both the cation and anion unlike in the other three SAILs. It is inferred that there is a contrasting variation between SAIL-2 and SAIL-3 toward induction of changes in the 2°structure of βLG, whereas both of these SAILs behaved almost similarly toward another globular protein, BSA.…”
Section: Spectroscopic Investigations Into Complexationmentioning
confidence: 99%
“…Two possible explanations for the decrease in fluorescence values are ethanol-induced changes to the globular structure of the whey proteins and competitive inhibition of ANS by ethanol. The effect of ethanol on the structure of β-lactoglobulin has been reported by Mousavi et al (2008). In their study, conducted at room temperature, ethanol had no effect on the intrinsic fluo- rescence of the protein.…”
Section: Extrinsic Fluorescencementioning
confidence: 76%
“…However, it did have an effect on the retinol binding ability of the protein. Mousavi et al (2008) found no binding at ethanol concentrations >40% (vol/vol), which was attributed either to radical structural refolding of the protein or to competition by ethanol. In our experiments, the fluorescence of the whey proteins increased as the ethanol concentration of the samples increased, but showed little temperature effect.…”
Section: Extrinsic Fluorescencementioning
confidence: 93%